The relationship between the human development index, free time and weekly hours worked by the Brazilian population (2017)
This study aims to analyze the evolution of the weekly working hours (WWH) of the Brazilian population in relation to its free time and the Human Development Indicator (HDI) from 2008 to 2012. In this study, data were collected from the National Sample Household Survey (NSHS) and from the United Nations Development Programme for Development (PNUD). The data were systematically compared by determining the temporal correlations between the HDI, WWH, housework and Brazilian workers’ free time. A gender subgroup was analysed in order to observe different inferences for each of these categories and its relationship with work. The results show that the HDI is directly proportional to the WWH for women and inversely proportional to the WWH for men. It was also found that the number of weekly working hours was higher for women than it was for men. Over the years, women have made a greater contribution to the development of the HDI than men, mainly due to increases in their presence in the labour market, combined with the reduction in gender inequality in society.